Experimental and numerical simulation of arced trapezoidal piano key weirs. (August 2019) - Karimi Chahartaghi, Mohammad; Nazari, Sohrab; Mahmoodian Shooshtari, Mohammad
Abstract: Piano key weirs are high performance labyrinth weirs particularly at lower heads (water height over the weir). These weirs are considered a recent development in terms of application and research. This study was conducted to numerically and experimentally investigate the hydraulic performance of arced trapezoidal piano key weirs ATPKW under different hydraulic and geometric conditions. The main purpose was to investigate the effect of the planform arc angle on the weir's hydraulic performance. To this end, four LRPKW models as well as four ATPKW models were studied. Due to the complexities associated with flow over piano key weirs, numerical models were used to simulate the flow pattern over the weir. Comparison of the results obtained for the ATPKW and LRPKW models indicated that, at upper heads, the ATPKW models offered a higher hydraulic performance than the LRPKW models. On the other hand, LRPKW model indicated better performance at lower heads. In addition, it was found that reducing the planform arc angle from 90° to 45° caused an initial reduction in the discharge coefficient, after which it dramatically increased. Also, LRPKW models indicated a more effective length and a more appropriate performance.